Evaluasi Kinerja Personil dalam Upaya Penanggulangan Kejadian Kebakaran (Studi Kasus Posko Kemuning pada Dinas Pemadam Kebakaran dan Penanggulangan Bencana Kota Palembang) - Imam Sufardi; Sunarto Sunarto; Muhammad Abduh (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Imam Sufardi Sunaryo, Evaluation of Personnel Performance in Efforts to Overcome Fire Incidents (Case Study of the Kemuning Command Post at the Palembang City Fire and Disaster Management Service). This study aims to analyze the performance of personnel in disaster management efforts (Case Study of the Kemuning Command Post at the Palembang City Fire and Disaster Management Office). The study used qualitative methods with data collection, namely observation, interviews and documentation. The results of the study indicate that the personnel have tried to do a good job in accordance with the SOP or applicable regulations, but on the other hand the personnel also continue to learn and practice in self-development and personal quality improvement by improving the quality of individuals which are expected to have an impact on the institution in service to public. The firefighters, especially the kemuning post, have done a good job, where the fact is that from time to time the personnel continue to learn and make improvements to their performance, by improving the quality of service for the fire service, especially the kemuning post. Every time from year to year there are always improvements and improvements both in terms of increasing human resources with training every time, there are also improvements in terms of facilities and infrastructure that continue to be added and improved, with the aim of improving the quality of the institution's services. The result is maximum, but technical and method problems in the field, of course, there are still many gaps that must be made for improvements that should be minimized in the future. The supporting factors in this research, namely the existence of training and training attended by personnel, are an important factor to improve the performance of Pos Kemuning personnel. While the inhibiting factor is the lack of supporting facilities such as cars and others.